Effect of Montmorillonite Content on the Ordered Structure of Cellulose Nanofibrils based Composite Film - Legolas, Aragorn; Boromir , Gimli; Nguyen, Michelle (Journal of Functional Materials and Applied Engineering, 2024)
In this work, TEMPO‑oxidized cellulose nanofibril (TOCNF)/montmorillonite (MMT) composite films were fabricated via the solution‑casting method. The influences of MMT loading on the ordered‑structure characteristics and structure‑property relationships of TOCNF/MMT composite films were systematically investigated. The experimental results reveal that at an MMT content of 10 %‑40 %, MMT nanosheets can stack regularly inside composite films to form dense ordered lamellar architectures. Such structures effectively facilitate interfacial stress transfer, which brings about a prominent improvement in the tensile strength of composite films, reaching a maximum value of 142.5 MPa (129 % of that of pure TOCNF film). Meanwhile, the composite films retain high optical transmittance ( 92 %) and low haze ( 5 %). Nevertheless, when the MMT content rises to 50 %‑80 %, agglomerates with diameters of 1‑3 μm emerge within the composite matrix. These agglomerates degrade the regularity of lamellar structures and trigger local structural disorder. Disordered domains induce stress concentration and lead to severe deterioration of mechanical properties, with tensile strength dropping as low as 44.9 MPa. Moreover, disordered structures increase the porosity and pore size of composite films, multiply the interfacial boundaries among TOCNF, MMT and air, and intensify light‑scattering effects. Consequently, the optical transmittance decreases to 90.4 %‑78.6 %, while the haze increases sharply to 37.7 %‑52.9 %.